Home Experiment Program for Senior Mechanical Laboratory Course: A Laboratory Program during COVID-19 Pandemic - Fitri Endrasari; Djati Wibowo Djamari; Indro Pranoto (Universitas Pahlawan Tuanku Tambusai, 2022)
COVID-19 pandemic triggers the development of virtual methods in doing the experiments for laboratory classes. However, the virtual methods cannot give the students a hands-on learning experience they should get from laboratory classes. This paper aims to disseminate the Home Experiment program conducted by Mechanical Engineering study program of Sampoerna University. This program is established to allow students to conduct experiments at home so that they obtain the hands-on learning experience during the pandemic. The program is conducted through the Senior Mechanical Laboratory (SML) course, and the result from heat transfer experiment is discussed in this paper. Students are assigned to design the heat transfer experiment (guided by the lecturer), purchase the required components, assemble the components, and conduct the experiment. Aside from submitting a written report, students are also required to submit experimentation videos and present their work in a conference at the end of the semester. It is hoped that this program will become a study case for home-based learning which is crucial during the pandemic situation.